Sergejaus Kovaliovo veikla disidentiniame judėjime ir jo ryšiai su Lietuva. - Tichomirovas, Sergejus (Genocidas ir rezistencija, 2025)
Sergei Kovaliov, who joined the dissident movement in 1968, a year later became one of the most active members of the Initiative Group, the first organisation of the movement for human rights in the Soviet Union. He participated directly in writing and sending to the West several addresses by the Initiative Group. His activities in the organisation were an important page in his life.